MUḌĀRABAT AGREEMENT IN FINANCING SYSTEM BY SHARIĀH BANKS: A LESSON FROM BANK SUMUT SYARIAH - Isnaini Isnaini; Zakaria Bahari; Iman Jauhari (Kanun Jurnal Ilmu Hukum, 2023)
Muḍārabat agreement in financing system by shariāh banks supposedly refers to the freedom of contract (al-hurriyāt). However, Bank Sumut Shariāh as one of the shariāh banks in Indonesia apparently does not apply this principle in the financing schemes. This study presents an analysis of the use of muḍārabat agreement in the financing system, according to its justice and beneficial principles. The study was carried out through exploratory and descriptive observations, while the obtained data was analyzed using an in-depth descriptive content method. The results revealed that the bank intends to implement a non-shariāh agreement instead of muḍārabat agreement in the financing system. The agreement is supposedly constructed according to al-hurriyāt where both parties have fair and proportional obligations and rights. Expectedly, it will imply to the raise of other benefits and equities in the economic growth and financing system, especially to those of the small and medium scale enterprises.